2013
DOI: 10.56431/p-z599o7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on the Optical Properties of Mg Doped CdO Thin Films Deposited by Spray Pyrolysis

Abstract: Thin films of CdO and 9% Mg doped CdO doped have been prepared using spray pyrolysis technique. Transmission and absorption spectra were recorded in order to estimate these films. The deposited thin films were exposed to γ - rays. We have studied the transmission, absorptions and absorption coefficient as a function of photon energy before and after irradiation. The optical constants such as: reflectance, extinction coefficient, refractive index, real and imaginary parts of the dielectric constant and the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Converting equation this one gets: 2.303 log ( ) = αt …………………………………….……………………..………………………………. (12) The absorbance (A), then is defined as logarithm (base 10) of the reciprocal of transmittance T; A= -log (T) =log (1/T), Then α =2.303 ( ) ………………………………..….………………………….…………..…...…….…………. (13).…”
Section: R=mentioning
confidence: 99%
See 1 more Smart Citation
“…Converting equation this one gets: 2.303 log ( ) = αt …………………………………….……………………..………………………………. (12) The absorbance (A), then is defined as logarithm (base 10) of the reciprocal of transmittance T; A= -log (T) =log (1/T), Then α =2.303 ( ) ………………………………..….………………………….…………..…...…….…………. (13).…”
Section: R=mentioning
confidence: 99%
“…Some recent studies [10][11][12][13][14][15][16][17][18] showed the effects of irradiation on the optical and structural CdO thin films properties.…”
mentioning
confidence: 99%
“…Another is thermal evaporation technique where the thin films were turned into impure by magnesium [10]. In addition, the effect of gamma rays on the properties of CdO thin films tinged with Mg by thermal chemical spray technology was studied [11]. The spry pyrolysis technique was used to prepare cadmium oxide thin films doped with Mg and study the effect of Annealing Temperature on the Electronic Transitions [12].…”
Section: -Introductionmentioning
confidence: 99%